Implementasi Lapor Semanu Sebagai Sistem Pelaporan Kegiatan Perangkat Desa di Kalurahan Semanu-Gunungkidul - Muhammad Zakariyah; Moh. Ali Romli; Sulistyo Dwi Sancoko; Fatah Nur Saifullah; Taufiq Dwi Purnomo; Febri Nur Diansah; Ridwan Halim (Universitas Teknologi Yogyakarta, 2025)
The suboptimal system for reporting activities in Kalurahan Semanu potentially hinders efficiency and community participation. Limited access and a less structured reporting flow present obstacles to information dissemination. This community service activity aimed to develop and implement the Lapor Semanu System as a technology-based solution for reporting activities. The methods employed included a participatory approach in identifying needs, designing mobile and website systems, and training village officials and the community on system usage. Evaluation was conducted through observation and feedback questionnaires from training participants. The results of this activity include the creation of a prototype two-sided Lapor Semanu System and the successful execution of training that demonstrated enthusiasm and initial understanding from participants, although the allocation of training time was noted as an important consideration for future development. This system has the potential to enhance efficiency and community participation in reporting activities within Kalurahan Semanu.